'My colleagues wear blinkers . . . If they were trained, they would understand better'. Reflections on teacher education on inclusion in Cyprus. Issue 2 (23rd April 2012) - Symeonidou, Simoni; Phtiaka, Helen
<x xml:space="preserve">Abstract</x> This paper discusses fundamental theoretical issues in relation to education on inclusion. These issues inform core decisions about initial teacher education courses and in‐service teacher‐training programmes on inclusion. International and local discussions and research in this area formed the background for the design and implementation of a 2‐year funded research project whose aim was to record teachers' knowledge, attitudes and skills in relation to inclusion before developing an in‐service training programme that suited their profiles. The paper focuses on Greek‐Cypriot teachers' perceptions of their initial and in‐service teacher education on inclusion in Cyprus, as revealed by survey and interview findings. The findings are discussed with reference to relevant literature from Cyprus and other countries in an attempt to draw connections between teacher education, local culture and international practice. The paper concludes with a discussion of the argument that in‐service training programmes on inclusion are of central importance, not only for Cyprus but also for other countries. We argue that teachers' initial education does not guarantee a shared understanding of inclusive education; therefore, in‐service teacher‐training programmes need to be carefully planned and delivered to all schoolteachers to address both theoretical and practical aspects of inclusive education effectively.